Principal’s Strategy in Forming Good Character in Lantai Batu SDIT Students - Desrianti Desrianti; Miressa Amenu Mulis (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
Character is reflection of students’ personality that will form students’ daily behavior. Students who have the potential and quality as superior generations are reflected in good character. Therefore, character education is considered important to be improved by the school. This study aims to analyze the principal’s strategy in forming good characters in students of SDIT Lantai Batu, Kecamatan Lima Kaum, Kabupaten Tanah Datar. The method used in this research is a qualitative method in the form of a case study. Data collection technique used in this research was data condensation, data display, conclusion drawing and verification. The result of this study indicated that the principal applies several strategies in forming good characters in students, namely strategy of Strengthening Character Education, implementing integrated curriculum, extracurricular activities, learning faith and morality, visionary and transformational leadership styles of principals and story telling method.